أحكام البحث الاجتماعي في قانون رعاية القاصرين العراقي - الكوردي, أكرم زاده (unuversity of eloued- جامعة الوادي, 2021)
تتلخص هذه الدراسة في بيان الأجهزة المعنية القائمة بتقديم الرعاية الاجتماعية للقاصرين وتشكيلاتها ومهامها في القانون العراقي، وكذلك تعريف البحث الاجتماعي وتحديد مهام الشخص القائم به الذي هو الباحث الاجتماعي. كما ستعرض المؤسسة المالية التي تموّل الخدمات الاجتماعية التي تقدّم للقاصرين، كل ذلك في ضوء آخر التعديلات التي أجريت على قانون رعاية القاصرين والتعليمات التي صدرت . Abstract: This study summarizes in a statement of the concerned offices that provide social care for minors, their formations, and their tasks in Iraqi law. As well as defining social research and identifying the tasks of the person in charge who is the social researcher. It will also show the financial institution that funds the social services which provide for minors, all this in the light of the latest amendments made to the care of minors law and instructions issued.
Provisions Of Social Research In The Iraqi Minor Care Law
مقال
Keywords: البحث الاجتماعي، الباحث الاجتماعي، رعاية القاصرين، صندوق العناية بالقاصرين.; Social Research, Social Researfor Minors, and Minors Care Fundcher, Care